2021
DOI: 10.1186/s12879-021-06961-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends and predictive factors for treatment failure following artemisinin-based combination therapy among children with uncomplicated malaria in Ghana: 2005–2018

Abstract: Background Since the introduction of artemisinin-based combination therapy (ACT) in Ghana in 2005 there has been a surveillance system by the National Malaria Control Programme (NMCP) and the University of Ghana Noguchi Memorial Institute for Medical Research (UG-NMIMR) to monitor the therapeutic efficacy of ACTs for the treatment of uncomplicated malaria in the country. We report trends and determinants of failure following treatment of Ghanaian children with artesunate-amodiaquine (ASAQ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Also, mean hemoglobin levels significantly increased in all three sites after treatment with DHAP. These observations compare well with findings from previous Ghanaian studies (Abuaku et al, 2019;Abuaku et al, 2021) and studies from other African countries (Dama et al, 2018;Davlantes et al, 2018;Mandara et al, 2018;Raobela et al, 2018;Roth et al, 2018) demonstrating the effectiveness of ACTs in parasite and fever clearance as well as improving hemoglobin levels of uncomplicated malaria patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, mean hemoglobin levels significantly increased in all three sites after treatment with DHAP. These observations compare well with findings from previous Ghanaian studies (Abuaku et al, 2019;Abuaku et al, 2021) and studies from other African countries (Dama et al, 2018;Davlantes et al, 2018;Mandara et al, 2018;Raobela et al, 2018;Roth et al, 2018) demonstrating the effectiveness of ACTs in parasite and fever clearance as well as improving hemoglobin levels of uncomplicated malaria patients.…”
Section: Discussionsupporting
confidence: 91%
“…All children examined on day 3, the day used to assess artemisinin partial resistance (WHO, 2020), were aparasitemic suggesting an adequate response of parasites to dihydroartemisinin, and supporting the observation that artemisinin resistance is currently not a problem in Ghana (Abuaku et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…Ghana adopted ACTs as the frontline treatment of uncomplicated falciparum malaria in 2005. Subsequent efficacy studies conducted in many sentinel sites of Ghana showed high efficacies of AL and AS-AQ with 28-day PCR-corrected cure rates above 90% (Abuaku et al, 2012;Abuaku et al, 2016;Abuaku et al, 2017;Abuaku et al, 2019;Abuaku et al, 2021). In addition, the imported falciparum cases among the Chinese workers returning from Ghana also responded well to the DHA-PPQ treatment with a 100% 28-day cure rate (not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Drug-resistant malaria and bacterial pathogens have already been identified in Ghana [28][29][30][31][32][33][34] and the distribution of antimicrobials has yet to be comprehensively studied.…”
Section: Introductionmentioning
confidence: 99%